Evaluating the potential of process sites for waste heat recovery. (1st January 2016) - Oluleye, Gbemi; Jobson, Megan; Smith, Robin; Perry, Simon J.
Highlights: Analysis considers the temperature and duties of the available waste heat. Models for organic Rankine cycles, absorption heat pumps and chillers proposed. Exploitation of waste heat from site processes and utility systems. Concept of a site energy efficiency introduced. Case study presented to illustrate application of the proposed methodology. Abstract: As a result of depleting reserves of fossil fuels, conventional energy sources are becoming less available. In spite of this, energy is still being wasted, especially in the form of heat. The energy efficiency of process sites (defined as useful energy output per unit of energy input) may be increased through waste heat utilisation, thereby resulting in primary energy savings. In this work, waste heat is defined and a methodology developed to identify the potential for waste heat recovery in process sites; considering the temperature and quantity of waste heat sources from the site processes and the site utility system (including fired heaters and, the cogeneration, cooling and refrigeration systems). The concept of the energy efficiency of a site is introduced – the fraction of the energy inputs that is converted into useful energy (heat or power or cooling) to support the methodology. Furthermore, simplified mathematical models of waste heat recovery technologies using heat as primary energy source, including organic Rankine cycles (using both pure and mixed organics as working fluids), absorption chillers and absorption heat pumps are developed to support the methodology. These models are applied to assess the potential for recovery of useful energy from waste heat. The methodology is illustrated for an existing process site using a case study of a petroleum refinery. The energy efficiency of the site increases by 10% as a result of waste heat recovery. If there is an infinite demand for recovered energy (i.e. all the recoverable waste heat sources are exploited), the site energy efficiency could increase by 33%. The methodology also shows that combining technologies into a system creates greater potential to exploit the available waste heat in process sites.